2008
DOI: 10.1111/j.1365-2338.2008.01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Pests of the palm (Palmae sp.) and date palm (Phoenix dactylifera) determined in Turkey and evaluation of red palm weevil (Rhynchophorus ferrugineus Olivier) (Coleoptera:Curculionidae)

Abstract: This paper covers the palm (Palmae sp.) and date palm (Phoenix dactylifera) pests which were determined by studies conducted in Turkey between 1941 and 2006. In total 15 species have been found to date: 1 belonging to Coccidae, 9 to Diaspididae, 1 to Margarodidae and 2 to Pseudococcidae families of the order Homoptera and 1 species to Scarabaeidae and 1 to Curculionidae families of the order Coleoptera. Among these pests, red palm weevil (Rhynchophorus ferrugineus Olivier) has caused a great deal of damage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 1 publication
0
14
0
1
Order By: Relevance
“…Red palm weevils were first described in 1891 in India (Lefroy, 1906;Vidyasagar, 1998) and are currently found in other parts of Asia, Africa, the Caribbean, Europe, Oceania, and North America (Netherlands Antilles) (Murphy & Briscoe, 1999;Bozbuga & Hazir, 2008;EPPO, 2008EPPO, , 2011Borchert, 2009;Pelikh, 2009). In southern China, the increasing transport of ornamental palm plants has resulted in the introduction of RPW into Hainan, Guangdong, Fujian, Taiwan, Guangxi, Yunnan, Hong Kong, Jiangxi, Shanghai, and Zhejiang (Ju et al, 2006;Wang, 2007;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Red palm weevils were first described in 1891 in India (Lefroy, 1906;Vidyasagar, 1998) and are currently found in other parts of Asia, Africa, the Caribbean, Europe, Oceania, and North America (Netherlands Antilles) (Murphy & Briscoe, 1999;Bozbuga & Hazir, 2008;EPPO, 2008EPPO, , 2011Borchert, 2009;Pelikh, 2009). In southern China, the increasing transport of ornamental palm plants has resulted in the introduction of RPW into Hainan, Guangdong, Fujian, Taiwan, Guangxi, Yunnan, Hong Kong, Jiangxi, Shanghai, and Zhejiang (Ju et al, 2006;Wang, 2007;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is essentially a pest of palms that has been reported by many countries, and it can also attack sugarcane (Bozbuga and Hazir 2008). In China, red palm weevil was Þrst reported in 1997 in Guangdong.…”
mentioning
confidence: 99%
“…Similar results have also been reported in previous studies by Kumar et al (2004), who investigated the infestation of RPW and found higher infestation in the months of June and July. While infestation of RPW was also higher in the months of February andMarch 2007 and2008, this might be due to removal of sucker in these months Ferry and Gomez (2002). The least attack (8%) of RPW was in the months of January, September, October, November and December in both the years 2007 and 2008.…”
Section: Discussionmentioning
confidence: 95%
“…Date palm (Phoenix dactylifera L. family: Arecaceae) is the most important fruit tree of tropical and sub-tropical regions of the world, this tree is evergreen and can reach up to 30 meters tall (height). Date palm is widely grown for its fruit in Iraq, Iran, India, Mediterranean, North Africa Countries, Oman and Pakistan (Azam et al, 2001;Bozbuga and Hazir, 2008;Khushk, 2005). Date palm is also found in the countries like America, Argentina, Bangladesh, Brazil, Cyprus, Nagaland, North, Pakistan (Khushk, 2005) Peru and Spain.…”
Section: Introductionmentioning
confidence: 99%